The complete tales : the 23 original Peter Rabbit books & 4 unpublished works - Potter, Beatrix, 1866-1943 (Penguin ; F. Warne, 1997)
A collection of stories relating all the adventures of Peter Rabbit, his mischievous cousin, Benjamin Bunny, and other Beatrix Potter characters.